Isotope engineering of silicon - Jackson, Jacoby (Kansas State University, 2019)
Isotopically engineering silicon to achieve nearly 100% pure ²⁸Si crystals has been researched for use in metrology, quantum computing, and in silicon-based integrated circuits. Silicon is naturally composed of three isotopes: ²⁸Si, ²⁹Si, and ³⁰Si with a relative abundance of 92.2%, 4.7%, and 3.1%, respectively. Use of isotope engineering of silicon was explored in the International Avogadro Project to define Avogadro’s constant. The silicon employed for this project must be as isotopically and chemically pure as possible to reduce defects in the crystal lattice. Isotope engineered silicon has also been researched for utilization in quantum computing. A proposal by B.E Kane has phosphorous donor atoms imbedded in silicon. The nuclear spin of the phosphorous atoms are the qubits for this scheme. Phosphorous has a nuclear spin (I=±1/2) and ²⁸Si does not. Isotopically engineered silicon is needed for this scheme to reduce the concentration of ²⁹Si, which also has a nuclear spin of I=±1/2 and is a major source of decoherence. The isotope composition of silicon also affects its phonon related properties. Thermal conductivity is of interest due to the increasing importance of heat management in integrated circuits. Isotopically engineered silicon has a thermal conductivity ten times higher than that of silicon of natural composition at 24 K and is 8% higher at room temperature.
Keywords: Isotope silicon; Quantum computing; Thermal conductivity